Beginnings of learning - "Krishnamurti, J" (London, 1975)
It is not that there must be an end to seeking, but rather the beginning of learning. Learning is far more important than finding." "As long as education is concerned merely with the culture of the outer... the inner movement with its immense depth will inevitably be for the few and in that there lies great sorrow. Sorrow cannot be solved, cannot be understood when you are running with tremendous energy along the superficial. Unless you solve this with self-knowing you will have revolt after revolt, reforms which need further reformation, and the endless antagonism of man against man will go on." "The heart of the matter is education, it is the total understanding of man and not an emphasis on one fragment of his life... All the enthusiasts for outward change always brush aside the more fundamental issues.
Keywords: Learning